Effects of Activated Carbon on Reduction in Pesticide Residues in Lettuce Grown in Soil Treated with Cyantraniliprole and Fluopyram - Kim, Seon Hwa; Lim, Da Jung; Yoon, Jihyun; Kim, In Seon (MDPI AG, 2025)
Reducing pesticide residues in crops is essential to ensure food safety, protect human health, and promote environmental sustainability. In this study, activated carbon (AC) was applied as a soil amendment to investigate its effect on reducing residues of the pesticides cyantraniliprole and fluopyram in greenhouse-grown lettuce. The effectiveness of AC in reducing pesticide residues varies significantly based on pesticides and crops. Pesticide dissipation patterns in the soil and a set of pesticide residues of lettuce leaf and root tissues, as well as the soil surrounding the roots for each of the tested pesticides, were analyzed using liquid chromatography with tandem mass spectrometry (LC-MS/MS) during the test periods. The results showed different pesticide dissipation patterns for cyantraniliprole, fitting the first-order kinetics, and fluopyram. Nevertheless, both AC treatments exhibited a similar decreasing tendency in which cyantraniliprole residues ranged from 0.050 to 0.064 mg/kg in leaf and 0.019 to 0.034 mg/kg in root samples, while fluopyram residues ranged from 0.168 to 0.509 mg/kg in leaf and 0.315 to 0.787 mg/kg in root samples. The highest percentage reductions were 71.3% and 77.3% for cyantraniliprole in leaf and root samples, respectively, and 79.7% and 87.5% for fluopyram in leaf and root samples. In addition, the soil samples showed a more dynamic pattern of pesticide residues compared to those of the lettuce samples. The overall findings suggest that applying AC as a soil amendment in pesticide-treated soils has a positive effect on reducing residues of cyantraniliprole and fluopyram in lettuce. Therefore, this AC-treated soil amendment could be considered a safer agricultural practice with great potential for producing safer food resources from pesticide-contaminated soils. Thus, it is expected that proper utilization of AC plays an important role in the production of safe agri-food products to manage and generate a sustainable agricultural environment.